An Investigation on Sharia Governance in Islamic Banking A Case of Islamic Banks in Oman - Al-Musheifri, Ziyad Juma (Advances in Social Sciences Research Journal, 2021)
The concept of Sharia governance in Islamic banks in Oman was highlighted by presenting the conceptual framework for Sharia governance and regulating the Islamic banks through Sharia governance. Finally, the study explains the role of Sharia governance in raising the efficiency of Islamic banks. As this research paper concluded that Sharia governance has a major role in Islamic banks, through the existence of a Sharia supervisory body on all transactions that take place inside these banks, which prevents the occurrence of any activities that violate the provisions of Islamic law, as happens in other banks. The Sharia Supervisory Board for Muzn is the highest authority in the bank with regard to all matters related to Islamic law. It ensures that the commission’s decisions are strictly followed. The Sharia Supervisory Board reviews product papers, structures, policies, and legal documents and all other tasks. The board also provides decisions based on Sharia in all matters and related banking issues, including opinion on all aspects of the bank's commitment to Islamic law. The findings indicated that Sharia governance laws must be applied by Islamic banks and they need to make updates through the SSB and AAOIFI boards. Sharia was found to be a regulatory and supervisory component that Islamic banks must operate under to ensure the religion has been applied within the establishment of the banks.